2011
DOI: 10.1007/s10554-011-9933-z
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic echocardiographic guidance during transcatheter closure of atrial septal defects in children and adults

Abstract: The purpose of this study was to evaluate the safety and efficacy of transcatheter atrial septal defect (ASD) closure guided by transthoracic echocardiography (TTE). Since 2004, ASD closure was performed successfully in total 337 patients. Transthoracic echocardiography guidance was used in 206 patients (61.1%) (group 1). Closure was guided by transesophageal echocardiography under general anesthesia in patients with poor transthoracic acoustic windows, defects with aneurysmatic septum and/or multiple defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 22 publications
7
27
0
Order By: Relevance
“…Our main finding is that in experienced hands, 2D-TTE associated with balloon-sizing is a valuable alternative to 2D-TEE for ASD closure guidance. Our results are in accordance to other groups (30,31). TTE-guidance is not universally accepted and published data are limited to either small series or selected patients (10)(11)(12).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our main finding is that in experienced hands, 2D-TTE associated with balloon-sizing is a valuable alternative to 2D-TEE for ASD closure guidance. Our results are in accordance to other groups (30,31). TTE-guidance is not universally accepted and published data are limited to either small series or selected patients (10)(11)(12).…”
Section: Discussionsupporting
confidence: 90%
“…Our results are in accordance to other groups (30,31). TTE-guidance is not universally accepted and published data are limited to either small series or selected patients (10)(11)(12). However one monocenter prospective randomized study suggested non-inferiority of 2D-TTE compared to 2D-TEE in 40 selected children (11).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations